Translating Cultural Safety to the UK - Lokugamage, Amali U. (Journal of medical ethics, 2023)
Disproportional morbidity and mortality experienced by ethnic minorities in the UK have been highlighted by the COVID-19 pandemic. The ‘Black Lives Matter’ movement has exposed structural racism’s contribution to these health inequities. ‘Cultural Safety’, an antiracist, decolonising and educational innovation originating in New Zealand, has been adopted in Australia. Cultural Safety aims to dismantle barriers faced by colonised Indigenous peoples in mainstream healthcare by addressing systemic racism. This paper explores what it means to be ‘culturally safe’. The ways in which New Zealand and Australia are incorporating Cultural Safety into educating healthcare professionals and in day-to-day practice in medicine are highlighted. We consider the ‘nuts and bolts’ of translating Cultural Safety into the UK to reduce racism within healthcare. Listening to the voices of black, Asian and minority ethnic National Health Service (NHS) consumers, education in reflexivity, both personal and organisational within the NHS are key. By listening to Indigenous colonised peoples, the ex-Empire may find solutions to health inequity. A decolonising feedback loop is required; however, we should take care not to culturally appropriate this valuable reverse innovation.